Use of polyaluminium chloride in studies of water supply treatability through coagulation, flocculation, and sedimentation - Kamiwada, Wagner Yukio [UNESP]; Andrade, Priscila Vega [UNESP]; Reis, Adriano Goncalves dos [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2020)
Polyaluminium chloride (PAC) is a pre-hydrolyzed inorganic polymeric coagulant that is being used widely in the treatment of water supply and wastewater by forming a hard and heavy Al(OH)(3)* precipitate, in addition to having a smaller effect on pH. The literature, however, is still scarce in correlating the chemistry and physics of the coagulant with process optimizations. The objective of this paper is to use PAC in studies of water supply treatability through coagulation, flocculation, and sedimentation. For this purpose, a mathematical modeling was initially performed to adjust turbidity and pH, and then remaining turbidity and apparent color coagulation diagrams were constructed with a pH of 4.0 to 9.0 and a dosage of 10 to 120 mg.L-1 of PAC (0.6 to 6.9 mg.L--(1) of Al3+). Different gradients of velocity and mixing times for coagulation and flocculation were also studied. The coagulation diagrams indicated satisfactory results in the pH range between 7 and 9 with a dosage higher than 30 mg.L of PAC (1.7 mg.L--(1) of Al3+), and it is related to the minimum solubility of Al(OH)(3)*. Coagulation and flocculation optimizations achieved an improvement of up to 79% in the remaining turbidity, a reduction of up to 83% in the settler area or a reduction of up to 67% in PAC dosage, due to an increase in the size of the floc produced. An in-depth knowledge of the chemistry and physics of the process related to the use of PAC can, therefore, bring benefits to its use.
Keywords: coagulation diagram; polyaluminium chloride; PAC; process optimization